Association of NT-proBNP level with severity in Acute Ischemic Stroke Patients (Bangladesh Journal of Medicine, 2026)
Background: This study was aimed to assess association of NT-proBNP levels with severity in acute ischemic stroke patients which may help in severity assessment of these patients. Methods: This casecontrol study was conducted in the Department of Neurology, Sir Salimullah Medical College Mitford Hospital, Dhaka, Bangladesh from November, 2023 to October, 2024.Total 100 subjects were enrolled in this study. Among this, 50 acute ischemic stroke patients with history within 3 days and confirmed by CT scan of head or MRI of brain were selected purposively from the Neurology Department of Sir Salimullah Medical College Mitford Hospital, Dhaka, Bangladesh. Another 50 age and gender matched subjects were selected from this place for comparison. Venous blood samples were collected from these patients and analyzed for estimation of plasma NT-proBNP. Results: This study found mean plasma NT-proBNP level was significantly higher (333.0±221.9pg/ml) in acute ischemic stroke patients (Case group) than control group (109.4±131.1pg/ml). A moderately strong positive correlation was observed between plasma NT-pro BNP level and NIHSS score at admission (r = 0.566; p